Controllable modulation of precursor reactivity using chemical additives for systematic synthesis of high-quality quantum dots - Park, Joonhyuck; Jayaraman, Arun; Schrader, Alex W.; Hwang, Gyu Weon; Han, Hee-Sun (Nature Publishing Group, 2020)
The optical and electronic performance of quantum dots (QDs) are affected by their size distribution and structural quality. Although the synthetic strategies for size control are well established and widely applicable to various QD systems, the structural characteristics of QDs, such as morphology and crystallinity, are tuned mostly by trial and error in a material-specific manner. Here, we show that reaction temperature and precursor reactivity, the two parameters governing the surface-reaction kinetics during growth, govern the structural quality of QDs. For conventional precursors, their reactivity is determined by their chemical structure. Therefore, a variation of precursor reactivity requires the synthesis of different precursor molecules. As a result, existing precursor selections often have significant gaps in reactivity or require synthesis of precursor libraries comprising a large number of variants. We designed a sulfur precursor employing a boron-sulfur bond, which enables controllable modulation of their reactivity using commercially available Lewis bases. This precursor chemistry allows systematic optimization of the reaction temperature and precursor reactivity using a single precursor and grows high-quality QDs from cores of various sizes and materials. This work provides critical insights into the nanoparticle growth process and precursor designs, enabling the systematic preparation of high-quality QD of any sizes and materials. Synthesis of high crystal quality quantum dots (QDs) requires optimization of reaction temperature and precursor reactivity. Here, the authors report precursor chemistry that enables controllable modulation of precursor reactivity using chemical additives, and systematically grow high-quality QDs from cores of various sizes and materials.